Treatment of multiple recessions with collagen matrix versus connective tissue: a randomized clinical trial - Rodrigo NAHAS; Valéria GONDIM; Cassio Volponi CARVALHO; Luis Marcelo CALDERERO; Ecinele Francisca ROSA; Thaís SAKIYAMA; João Batista CÉSAR NETO; Cláudio Mendes PANNUTI; Giuseppe Alexandre ROMITO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The objective of this study was to determine whether collagen matrix (CM) is an alternative to connective tissue graft technique (CTG) in the treatment of multiple gingival recessions (GR). The indication of CM for the treatment of multiple GR is not yet clear. More studies are needed to better understand this treatment modality, as an alternative to CTG. In this single-blind, split-mouth randomized clinical trial, fifteen patients with multiple Miller class I upper GR were selected and randomly assigned to control group (CTG) or test group (CM). Root coverage (RC) and patient-centered outcomes were evaluated at baseline and after 3, 6, and 12 months. A total of 82 GRs were treated. There was no significant difference regarding GR depth (GRD, primary outcome) between CTG (0.5 ± 0.9 mm) and CM groups (0.6 ± 1.0 mm) (p = 0.225). Percentage of RC was 82.14% in CTG and 77.7% in CM. Both groups demonstrated a gain in keratinized tissue width at 12 months (p < 0.05). Dentine hypersensitivity was effectively reduced in both groups. Postoperative pain was significantly higher in the CTG (p = 0.001). Esthetic satisfaction was high for both groups, with no significant difference (p > 0.05) between groups. After 12 months, both surgical treatments were able to promote RC, and GRD was similar in both CTG and CM groups.